Convergence in Islamic financial development: Evidence from Islamic countries using the Fourier panel KPSS stationarity test - M. Kabir Hassan; Hasan Kazak; Uğur Adıgüzel; Mehmet Akif Gunduz; Ahmet Tayfur Akcan (Borsa Istanbul Review, 2023)
This study investigates whether there is convergence among Islamic countries with respect to the relationship between growth in Islamic financial markets and economic growth in those countries as measured by Gross Domestic Product. We use data from 2013 to 2021 for the nine Islamic countries with the highest levels of activity in Islamic finance. We employ the Fourier Panel KPSS Stationarity Test to examine the convergence hypothesis for four indicators of Islamic financial markets activity: Islamic Financial Asset Volume (IFAV), Islamic Banking Asset Volume, Sukuk Outstanding Volume, and Takaful Contribution Volume. Our analysis reveals that only IFAV exhibits convergence, while the other indicators do not. We also evaluate country-specific convergences within each indicator and find different results. Our study provides essential guiding findings regarding the significance of Islamic finance growth for countries and their prospects.